Production data analysis of shale gas using fractal model and fuzzy theory: Evaluating fracturing heterogeneity. (15th September 2019) - You, Xu-Tao; Liu, Jian-Yi; Jia, Chun-Sheng; Li, Jun; Liao, Xin-Yi; Zheng, Ai-Wei
Highlights: New conversion relationship of gas-liquid flow fractal dimension is proposed. New fractal seepage model of multistage fracture networks is established. The phenomenon of peak gas production in shale-gas wells is analyzed. An evaluation method for fracturing heterogeneity is established. Calculation accuracy of gas production by heterogeneous model is improved by 15%. Abstract: The development of shale-gas reservoirs has been dramatically accelerated with the technical breakthroughs made in the fields of horizontal well drilling and multistage hydraulic fracturing. After being restructured by hydraulic fracturing, the shale reservoir would have a complicated fracture network featuring great randomness. The accurate evaluation of the fracture network structure and the quantitative calculation of the fracturing fluid flowback are keys to the efficient development of shale-gas fields. In this paper, a new fractal seepage model of single fracturing section was established based on the conversion relationship of gas-liquid flow fractal dimension. Then, the sensitivity of model parameters and the flow characteristics of single fracture section were analyzed to determine the reason that gas production "rises first, and then drops down" at the initial production phase. Finally, the mathematical description of the heterogeneity of fracture networks was further proposed based on Fuzzy theory. Case studies in Fuling shale-gas field were performed by means of the Extended Monte Carlo Simulation and the optimal fracturing heterogeneity factors of typical wells are 0.25, 0.10 and 0.15. Compared with the homogeneous model, the accuracies of gas production and water production calculated by heterogeneous model are increased by up to 15% and 20%, respectively.